2016
DOI: 10.1177/1084822316639032
|View full text |Cite
|
Sign up to set email alerts
|

Community-Level Association Between Home Health and Nursing Home Performance on Quality and Hospital 30-Day Readmissions for Medicare Patients

Abstract: We evaluated whether community-level home health agencies and nursing home performance is associated with community-level hospital 30-day all-cause risk-standardized readmission rates for Medicare patients used data from the Centers for Medicare & Medicaid Service from 2010 to 2012. Our final sample included 2,855 communities that covered 4,140 hospitals with 6,751,713 patients, 13,060 nursing homes with 1,250,648 residents, and 7,613 home health agencies providing services to 35,660 zipcodes. Based on a mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Better performance may lead to better care. The association between nursing home and home health performance in quality of care and outcomes has been studied . For example, one study found that individuals receiving care in higher‐quality skilled nursing facilities had lower readmission rates (18%) than those in lower‐quality skilled nursing facilities (22%) .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Better performance may lead to better care. The association between nursing home and home health performance in quality of care and outcomes has been studied . For example, one study found that individuals receiving care in higher‐quality skilled nursing facilities had lower readmission rates (18%) than those in lower‐quality skilled nursing facilities (22%) .…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study found that individuals receiving care in higher‐quality skilled nursing facilities had lower readmission rates (18%) than those in lower‐quality skilled nursing facilities (22%) . Another study found that improving nursing home and home health performance was associated with lower community‐level risk‐standardized readmission rates . The existing standard is that all agencies should achieve the highest score for quality care.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations